CHAQ2020 - Hope Bay - Spatial data - Westin, Jonathan; Almevik, Gunnar (University of Gothenburg, 2021)
The first Swedish Antarctic Expedition (1901-1903), led by Otto Nordenskjöld, sailed to Antarctica on the ship Antarctic captained by CA Larsen, and established a research station on Snow Hill Island. There six members overwintered and performed paleontological, meteorological, geomagnetic and geological studies, while the rest of the expedition set sail for South Orkney.

After the winter, on the way back to Snow Hill Island, the Antarctic got stuck in the ice and sank. At this point, the expedition members were divided into three groups. One of these overwintered an extra year on Snow Hill Island, whereas the other two groups were forced to build stone huts in order to overwinter at Hope Bay and Paulet Island. An Argentinean vessel, the Corbeta Uruguay, rescued the expedition in November 1903.

CHAQ 2020 is an Argentinean-Swedish project with fieldwork in the area around the Antarctic Peninsula aiming to investigating and documenting the historical remains of the first Swedish South Polar expedition under the leadership of Otto Nordenskjöld 1901-1903. The material was collected in January and February 2020.

This catalogue entry collects the spatial data from Hope Bay, which include point clouds and textured meshes produced through laser scanning with a Faro Focus m70, and structure-from-motion photography.

The 3d documentation of the stone shelter consists of two complete sets of structure-from-motion photography with two different cameras (Fujifilm X-T2 and iPhone XR), with approximately 1260 photos in the first set and 1870 photos in the second, and two complete sessions of laser scanning (Faro Focus m70) with 21-25 individual scanning positions in each session. The result from the laser scanning is published as three point clouds; one collecting all scans into one pointcloud, and a separate pointcloud for each session. The result from the structure-from-motion scanning is published as both point clouds and textured meshes.

Syftet med forskningsprojektet var att dokumentera lämningarna efter Otto Nordenskjölds Antarktisexpeditionen 1901-1903. Materialet består av fotografier, planer, ritningar, 3d-modeller och drönarfilmer från Snow Hillön, Hoppets vik och Seymourön.

Denna katalogpost samlar den spatiala datan från Hoppets vik, vilket inkluderar punktmoln och texturerade trådmodeller skapade med en Faro Focus m70 laserskanner samt structure-from-motion fotografering.

Se den engelska beskrivningen för mer information.

3D-dokumentationen av stenhyddan består av två kompletta uppsättningar av structure-from-motion fotografering med två olika kameror (Fujifilm X-T2 och iPhone XR), med cirka 1260 foton i första uppsättningen och 1870 bilder i den andra, och två kompletta laserskanningssessioner (Faro Focus m70) med 21-25 individuella skanningspositioner i varje session. Resultatet från laserskanningen publiceras som tre punktmoln; ett som samlar alla skanningar i ett moln och ett separat punktmoln för varje session. Resultatet från structure-from-motion fotograferingen publiceras både som punktmoln och texturerade trådmodeller.
CHAQ2020 - Hoppets vik - Spatiala data
Keywords: Antarctica; Antarktis; Antarctic region; Swedish Antarctic Expedition, 1901-1904; Första svenska Antarktisexpeditionen, 1901-1904; Nordenskjöld, Otto, 1869-1928; Nordenskjöld, Otto, 1869-1928; History and Archaeology; Historia och arkeologi; Structure; Byggnader och byggnadsanläggningar